Genome-wide association study for carcass traits in an experimental nelore cattle population - Medeiros De Oliveira Silva, Rafael [UNESP]; Stafuzza, Nedenia Bonvino [UNESP]; Fragomeni, Breno De Oliveira; Ferreira De Camargo, Gregório Miguel [UNESP]; Ceacero, Thaís Matos; Cyrillo, Joslaine Noely Dos Santos Gonçalves; Baldi, Fernando [UNESP]; Boligon, Arione Augusti; Mercadante, Maria Eugênia Zerlotti; Lourenco, Daniela Lino; Misztal, Ignacy; De Albuquerque, Lucia Galvão [UNESP] (Public Library of Science (PLoS), 2017)
The purpose of this study was to identify genomic regions associated with carcass traits in an experimental Nelore cattle population. The studied data set contained 2,306 ultrasound records for longissimus muscle area (LMA), 1,832 for backfat thickness (BF), and 1,830 for rump fat thickness (RF). A high-density SNP panel (BovineHD BeadChip assay 700k, Illumina Inc., San Diego, CA) was used for genotyping. After genomic data quality control, 437,197 SNPs from 761 animals were available, of which 721 had phenotypes for LMA, 669 for BF, and 718 for RF. The SNP solutions were estimated using a single-step genomic BLUP approach (ssGWAS), which calculated the variance for windows of 50 consecutive SNPs and the regions that accounted for more than 0.5% of the additive genetic variance were used to search for candidate genes. The results indicated that 12, 18, and 15 different windows were associated to LMA, BF, and RF, respectively. Confirming the polygenic nature of the studied traits, 43, 65, and 53 genes were found in those associated windows, respectively for LMA, BF, and RF. Among the candidate genes, some of them, which already had their functions associated with the expression of energy metabolism, were found associated with fat deposition in this study. In addition, ALKBH3 and HSD17B12 genes, which are related in fibroblast death and metabolism of steroids, were found associated with LMA. The results presented here should help to better understand the genetic and physiologic mechanism regulating the muscle tissue deposition and subcutaneous fat cover expression of Zebu animals. The identification of candidate genes should contribute for Zebu breeding programs in order to consider carcass traits as selection criteria in their genetic evaluation.